Nutritional composition and antioxidant properties of fruits and vegetables - Jaiswal, Amit K. (Academic Press, 2020)
Nutritional Composition and Antioxidant Properties of Fruits and Vegetables provides an overview of the nutritional and anti-nutritional composition, antioxidant potential, and health benefits of a wide range of commonly consumed fruits and vegetables. The book presents a comprehensive overview on a variety of topics, including inflorescence, flowers and flower buds (broccoli, cauliflower, cabbage), bulb, stem and stalk (onion, celery, asparagus, celery), leaves (watercress, lettuce, spinach), fruit and seed (peppers, squash, tomato, eggplant, green beans), roots and tubers (red beet, carrots, radish), and fruits, such as citrus (orange, lemon, grapefruit), berries (blackberry, strawberry, lingonberry, bayberry, blueberry), melons (pumpkin, watermelon), and more. Each chapter, contributed by an international expert in the field, also discusses the factors influencing antioxidant content, such as genotype, environmental variation and agronomic conditions. --